Droplet Evaporation Process of a Fluorobenzene + n-Octane + Polystyrene Mixture - Wei Wang; Zhendong Zhou; Bo Zhou (Molecules, 2023)
The vapor–liquid equilibrium of the fluorobenzene–polystyrene binary polymer solution at 303.15 K was measured using a static pressure device. The vapor–liquid equilibrium of the fluorobenzene–n-octane–polystyrene ternary solution in a partial concentration range under normal pressure was determined using an improved Othmer equilibrium still, in which the octane concentration was low. Three activity coefficient models, poly-NRTL, UNIQUAC, and M-UNIQUAC-LBY, were utilized to correlate the experimental data of binary and ternary solutions, and the component activities of the fluorobenzene–n-octane–polystyrene solution at 303.15 K were predicted. A mathematical model based on the Stefan flow was developed to simulate the evaporation process of composite spherical droplets. The activity predicted by the activity coefficient model was used for numerical simulations, and compared with simulations using the activity following Raoult’s law. The comparative analysis revealed that simulations based on Raoult’s law and activity coefficient models yielded similar results when the mass fraction of fluorobenzene exceeded 0.6. However, in the later stages of evaporation, the calculations based on Raoult’s law predicted a 10% shorter drying time for fluorobenzene. The activity coefficient models provided a better approximation and exhibited similar droplet diameter shrinking behaviors to the actual evaporation process.